1988
DOI: 10.1128/aac.32.1.134
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of PSE-2 beta-lactamase

Abstract: The nucleotide sequence of PSE-2 beta-lactamase, an enzyme that readily hydrolyzes both carbenicillin and oxacillin, has been determined. The deduced sequence of 266 amino acids contained 93 residues identical to those of OXA-2 beta-lactamase and the Ser-Thr-Phe-Lys tetrad also found in the active site of TEM-1 beta-lactamase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
88
0
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(89 citation statements)
references
References 17 publications
0
88
0
1
Order By: Relevance
“…Sequence analysis has shown that the larger probe contains 101 base pairs external to the PSE-2 gene that are 100% identical to the sequence proximal to the OXA-2 bla gene (7). Three of five strains falsely reacting with the 1.2-kb PSE-2 probe made (15,25) and has considerable amino acid sequence similarity with the OXA-2 enzyme (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence analysis has shown that the larger probe contains 101 base pairs external to the PSE-2 gene that are 100% identical to the sequence proximal to the OXA-2 bla gene (7). Three of five strains falsely reacting with the 1.2-kb PSE-2 probe made (15,25) and has considerable amino acid sequence similarity with the OXA-2 enzyme (7).…”
Section: Discussionmentioning
confidence: 99%
“…Probes for TEM-1 and OXA-2 are intragenic (4,31). An intragenic probe was also developed for the PSE-2 bla gene based on the recent determination of its DNA sequence (7).…”
Section: Methodsmentioning
confidence: 99%
“…b-Lactamases can be divided into four classes based on amino acid sequence homologies. [1][2][3] The class B enzymes are zincdependent metallo-b-lactamases that are structurally and mechanistically independent of the other three classes of active-site serine b-lactamases (A, C, and D). Homology searches combined with multiple sequence alignments have identified several common structural elements between active-site serine b-lactamases and PBPs.…”
mentioning
confidence: 99%
“…similar structure is consistent with its status as a lessevolved integron. The presence of such an element has been reported to be required on at least one of the sequences participating in the Int-mediated crossing over at the GTT sequence at crossover point 1 (28 (46), aacAlb (8), aadAl (49), aadA2 (36,38,53), aadB (43), dhfrII (52,62), dhfrV (49), oxa2 (19), aacAla (56), aacCl (61), cmUA (3), dhfrI (51), oxal (32), pse2 (20), pse4 (7), and merA (9) were from the respective references.…”
mentioning
confidence: 99%